การออกแบบวิธีการสร้างแฟ้มสัญลักษณ์แสดงตนสำหรับการสอบถามข้อมูลในระบบการจัดการฐานข้อมูลเชิงวัตถุ - มารุต ศิลปสุนทร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Using signature file method in an object-oriented database management system decreases time to access objects by direct traversal. Generally, a signature file is constructed in the target path which will be the condition in a query predicate. But the signature file does not cover all of the conditions of predicate. This research is aimed to design the new structure of signature file-Terminal virtual path and Non-Terminal virtual path-which store all object signatures of the aggregation hierarchy. With Terminal virtual path and Non-Terminal virtual path, everry predicate that occurs in any classes in the aggregation hierarchy can be queried. This method enhances the effectiveness of the path signature. We compare the effectiveness of Terminal virtual path and Non-Terminal virtual path signature with the traditional method-path signature in four database schemes. One is one path aggregation hierachy and the others are multi-path aggregation hierarchy. Terminal virtural path and Non-Terminal virtual path decrease both the searching time and false drop.